Impacts of Drug Abuse and Addiction and Effects of Pharmaceuticals Misuse: Review Article - Hiba Hussein Fadil Mahdi; Ghassan Jasim Mohammed (Journal of Biomedicine and Biochemistry, 2025)
This paper presents a historical overview of drug addiction since it follows its beginnings that stretch to 7000 years B.C, it also identifies different concepts related to drugs, including intoxicants, hashish, medicines, painkillers, volatile solvents, light addictive stimulants, and abused pharmaceuticals. In addition, this paper tackles the impacts of drug use, clarifies the relation between drugs, painkillers, and addiction, outlines the differences between drug users and addicts, and discusses the factors contributing to addiction. The paper takes a deep dive into drug addiction theories like the physiological theory, abuse prevention theory, commitment to tradition and social bonding, risk, and protective factors theory, and intrapersonal theory, and specifies the general effects and disorders associated with addictive substances, alcohol, and ethanol addicts' behavior and addiction disorders.